2023
DOI: 10.1186/s40359-023-01080-y
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and need to belong as moderators of the relationship between thwarted belongingness and suicidal ideation

Abstract: Background In the Interpersonal Theory of Suicide, thwarted belongingness is presented as a main predictor for suicidal ideation. Studies only partially support this prediction. The aim of this study was to examine whether the heterogenous results are due to moderating effects of attachment and the need to belong on the association between thwarted belongingness and suicidal ideation. Methods Four hundred forty-five participants (75% female) from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Most of industrial workers in Kuwait come from foreign countries and they leave their families and friends at the back. As reported by other scholars, humans feel psychologically better when they socialize with others (Allen et al , 2022; Dienst et al , 2023). Hence, participants who lived in shared houses, may have a chance to socialize and this might help them to have less psychological issues.…”
Section: Discussionsupporting
confidence: 64%
“…Most of industrial workers in Kuwait come from foreign countries and they leave their families and friends at the back. As reported by other scholars, humans feel psychologically better when they socialize with others (Allen et al , 2022; Dienst et al , 2023). Hence, participants who lived in shared houses, may have a chance to socialize and this might help them to have less psychological issues.…”
Section: Discussionsupporting
confidence: 64%
“…Based on this information, it is then possible to work with the patients on their individual experience of TB or PB, either interventionally or preventively in psychotherapy. For example, studies [ 58 ] show that both constructs are related to the need to belong, offering different starting points for psychotherapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One in ve suicides between 2003 and 2020 were associated with problems like romantic breakups, con ict, and divorce. Furthermore, research has shown that attachment styles and interpersonal problems can predict behaviours related to suicide (Dienst et al, 2023).…”
mentioning
confidence: 99%